2013
DOI: 10.7314/apjcp.2013.14.11.6221
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress in the Treatment of Metaplastic Breast Carcinoma

Abstract: Metaplastic breast cancer (MBC) is a rare type of breast carcinoma, characterized by various combinations of mesenchymal, adenocarcinoma and other epithelial components. MBC often manifests as a large mass, with low axillary lymph node involvement and poor prognosis. Knowledge and treatment patterns about MBC demographics, presentation and tumor characteristics are very limited. In clinical practice, MBC is usually treated based on the guidelines developed for infiltrating ductal carcinoma (IDC). The ideal tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Al Sayed et al and others reported that lymph node metastases only occurred in pure epithelial MBCs (Kurian et al, 2002;Al Sayed et al, 2006). It is recommended that axillary lymph node dissection is not required in spindle cell carcinoma or carcinosarcoma due to no risk of axillary lymph node involvement (Hu et al, 2013). However, only 4 out of 6 patients with lymph node metastasis had pure epithelial MBCs in our study.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Al Sayed et al and others reported that lymph node metastases only occurred in pure epithelial MBCs (Kurian et al, 2002;Al Sayed et al, 2006). It is recommended that axillary lymph node dissection is not required in spindle cell carcinoma or carcinosarcoma due to no risk of axillary lymph node involvement (Hu et al, 2013). However, only 4 out of 6 patients with lymph node metastasis had pure epithelial MBCs in our study.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, BCS, lumpectomy, local excision with cancer-free margins (≥3 cm) can be used in some appropriate patients (Hu et al, 2013). In our study, the most common presenting symptom was a palpable mass and the median tumor size at diagnosis was 3.5 cm (range, 1.5-12 cm).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The optimal therapy for chest wall tumors is surgical resection, in which local resection can be performed on benign or malignant tumors (Afsharfard et al, 2013;Alipour et al, 2014;Fouladi et al, 2014;Hu et al, 2013;Sedighi et al, 2013;Talaiezadeh et al, 2013;Zhu et al, 2013;Hu et al, 2014;Jia et al, 2014;Ozkan-Gurdal et al, 2014). However, the resection range should be properly enlarged to such tumors as desmoids, chondroma and osteoclastoma, or be resolved as in malignant tumors, though with benign pathological examinations (Errani et al, 2010;Nieuwenhuis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus HOTAIR whose expression level is a powerful predictor of metastases and survival rate in breast cancer (Gupta et al, 2010). In the aspect of treatment, exclusion of through molecular inhibitors (Hu et al, 2013), there may be other way. the curcumin can significantly inhibit the invasion and migration of multiple cancer cells by triggering epigenetic events (Balasubramanian et al, 2007).…”
Section: Long Non-coding Rnas Which Involved In Breast Cancermentioning
confidence: 99%